Avaliação de cursos de graduação com base no Sinaes: um estudo das dissertações e teses - Teixeira, Angelica Cavalcanti (2022)
This dissertation focuses on the analysis of productions carried out in graduate programs in the years 2005 to 2021, about the evaluations of higher education courses based on their framework in Sinaes. The objective is to examine what has been produced in this regard, that is, what are the authors' concerns and research approaches. To fulfill this purpose, we mapped the scientific production in relation to course evaluation in the database of the Brazilian Digital Library of Theses and Dissertation (BDTD), quantifying it in the established time frame. The analysis has as a parameter the content of dissertations and theses with regard to Sinaes guidelines in course evaluation and was made from the emerging categorization of the works, such categories will serve as a guide for our interpretation and discussion of the data. The examination of productions is based on content analysis, whose objective is to classify and categorize allocating the characteristics of the productions to key elements, so that they can be compared to other constituent elements of the object of investigation. The research is characterized as State of the art or State of knowledge as it focuses on mapping and discussing academic productions in different fields of knowledge. Regarding the research sample, the qualitative approach was more present, as for the type of research, the exploratory was the most evident and as for the means of research, the documentary was present in large part. Based on the analysis of the data obtained, we concluded that most productions criticize Sinaes, pointing out the weaknesses present in the instruments, dimensions and indicators, especially in relation to distance education. They refer to Sinaes as just a regulatory assessment, but there are data that point to a positive view of regulation. In view of the analysis of the study data, we can still conclude that most authors report that it is necessary to have an evaluation of higher education in relation to both classroom and distance courses, but that Sinaes needs adjustments in its methods and processes of evaluation. Assessment is necessary primarily so that we can guarantee the quality of higher education.